Study of physicochemical properties of oral fluid in persons with periodontal disease on the background of metabolic syndrome - Glushchenko Т. А. (Actual Dentistry, 2021)
Topicality. Over the past few years, scientists have attracted the attention of the problem of studying the relationship between metabolic syndrome and periodontal disease. Topics of risks associated with the association with various metabolic disorders have become one of the most important research topics in periodontology. Oral fluid plays a leading role in the proper functioning and maintenance of homeostasis of the entire periodontal tissue complex, is a mediator of the combination of its structures with the environment and an important nutrient substrate for the microflora of the oral cavity. The aim of the study. In order to study the quantitative and qualitative changes of oral fluid in periodontal diseases on the background of the metabolic syndrome, the rate of secretion of mixed saliva, its viscosity and acid-base balance were studied. 2 groups were formed for research: basic and comparative. Materials and methods. The main group included 30 people with inflammatory-dystrophic lesions of the periodontium on the background of metabolic syndrome, the comparison group consisted of 30 people with periodontal disease without endocrinological pathology. Results and discussion. The results of the study revealed homeostatic shifts in the oral biosystem of persons with periodontal disease on the background of metabolic syndrome: a decrease in salivation may indicate a violation of the secretory function of the salivary glands on the background of metabolic disorders, which naturally affected the increase in saliva viscosity. Conclusions. The predominance of acidosis in the oral cavity and the reduction of the protective properties of saliva becomes an important factor in creating a periodontopathogenic situation in the oral cavity and aggravating the course of periodontal disease in this category of patients.